The tumor and plasma cytokine profiles of renal cell carcinoma patients - Lee Moon Hee; Laajala Essi; Kreutzman Anna; Järvinen Petrus; Nisen Harry; Mirtti Tuomas; Hollmén Maija; Mustjoki Satu (NATURE PORTFOLIO, 2022)
Renal cell carcinoma (RCC) accounts for 90% of all renal cancers and is considered highly immunogenic. Although many studies have reported the circulating peripheral cytokine profiles, the signatures between the tumor tissue and matching healthy adjacent renal tissue counterparts have not been explored. We aimed to comprehensively investigate the cytokine landscape of RCC tumors and its correlation between the amount and phenotype of the tumor infiltrating lymphocytes (TILs). We analyzed the secretion of 42 cytokines from the tumor (n = 46), adjacent healthy kidney tissues (n = 23) and matching plasma samples (n = 33) with a Luminex-based assay. We further explored the differences between the tissue types, as well as correlated the findings with clinical data and detailed immunophenotyping of the TILs. Using an unsupervised clustering approach, we observed distinct differences in the cytokine profiles between the tumor and adjacent renal tissue samples. The tumor samples clustered into three distinct profiles based on the cytokine expressions: high (52.2% of the tumors), intermediate (26.1%), and low (21.7%). Most of the tumor cytokines positively correlated with each other, except for IL-8 that showed no correlation with any of the measured cytokine expressions. Furthermore, the quantity of lymphocytes in the tumor samples analyzed with flow cytometry positively correlated with the chemokine-family of cytokines, CXCL10 (IP-10) and CXCL9 (MIG). No significant correlations were found between the tumor and matching plasma cytokines, suggesting that circulating cytokines poorly mirror the tumor cytokine environment. Our study highlights distinct cytokine profiles in the RCC tumor microenvironment and provides insights to potential biomarkers for the treatment of RCC.